The Effects of International Monetary Flows on the Ecuadorian Economy from 2002 to 2021 - Miranda-Peña, Álvaro Steve (2024)
Ecuador’s economic expansion has been shaped by diverse external factors that have impacted its performance. This study investigated the correlation between external debt, foreign direct investment, and gross fixed capital formation in relation to Ecuador’s economic growth spanning from 2001 to 2021. Employing a quantitative approach, the research sourced data from various macroeconomic indicators of Ecuador’s Central Bank, and an econometric model of logarithmic linear regression was devised, grounded in the principles of ordinary least squares. This model facilitated an examination of the interrelationships among the variables of interest. The results obtained from the analysis indicated that both external debt and foreign direct investment wielded significant influence on economic growth. Specifically, external debt demonstrated a favorable effect on the dependent variable, whereas foreign direct investment displayed an adverse relationship, painting a less promising scenario for Ecuador’s economy.